1990
DOI: 10.1128/jb.172.5.2804-2807.1990
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and analysis of a 35.3-kilobase DNA region involved in exopolysaccharide production by Xanthomonas campestris pv. campestris

Abstract: Cosmid clones able to restore exopolysaccharide production in possibly insertion sequence element-induced surface mutants of Xanthomonas campestris pv. campestris were isolated. By fragment-specific Tn5-lac mutagenesis of one of the cosmids, pXCB1002, a new DNA region which is involved in exopolysaccharide biosynthesis and which is organized into at least 12 complementation groups was identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…In V. cholerae, Deleya marina and X. campestris pv. campestris, rough appearance has been linked to EPS production (Hotte et al, 1990;Shea et al, 1991;Wai et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In V. cholerae, Deleya marina and X. campestris pv. campestris, rough appearance has been linked to EPS production (Hotte et al, 1990;Shea et al, 1991;Wai et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…X. campestris IS element B100-2 is most probably the cause of an exopolysaccharide defect in at least two X. campestris pv. campestris exopolysaccharide mutants (18).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the EPS may play a role in the ability of Xanthomonas spp. to infect plants (58) have induced mutations affecting its EPS (2,6,26,28,33,38,60,65) and no definitive role of its EPS or cell surface molecules in virulence has been determined (2,9,17,29,36,44,48,59,61). Defects in the LPS of Rhizobium, Erwinia, and Pseudomonas species can lead to partial or complete loss of virulence (30,43,51).…”
Section: M28mentioning
confidence: 99%